Strategi dan Dampak Maqasid Syariah dalam Pemeliharaan Lingkungan Sekitar Kecamatan - Arman Maulana; Siti Rosmayati (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2021)
Maqashid Sharia requires the protection of life on earth and the relevance of environmental sustainability to the protection of the earth and all life on earth on the principles of Maqashid Sharia. Qualitative research to collect data through semi-structured interviews with company environmental officials. The survey results show that the strategy implemented by UPT DAS Citarik, Cicalengka District has succeeded in reducing environmental waste pollution into rivers and improving river water quality, which is an important step in protecting the environment and complying with the principles of Islamic teachings.